A storm or a storm in a teacup? A retrospective review of spontaneous pneumomediastinum at a tertiary Australian Hospital - Cox, Georgia T.; Bowles , Madison B.; Ng, Jessica; Townend, Philip; Rutherford, Leigh; Parker , David (International Surgery Journal, 2023)
Background: Spontaneous pneumomediastinum (SP) is defined as the presence of free air in the mediastinum without a clear precipitating cause. Whilst uncommon and with a relatively benign course, SP is often thoroughly investigated by surgeons as spontaneous oesophageal perforation (Boerhaave’s syndrome) must be identified early due to high morbidity and mortality. This study aimed to evaluate current practice in the investigation and management of SP at our institution. Methods: All patients with imaging-confirmed pneumomediastinum at a tertiary hospital from 2014 to 2022 were reviewed. Those with precipitating trauma, recent surgery or aerodigestive instrumentation were excluded. Results: 70 patients were included; 4 (5.7%) patients were diagnosed with Boerhaave’s syndrome based on computed tomography (CT) evidence of oesophageal injury alone and were treated with immediate surgery. The remaining 66 patients were diagnosed with SP. In this group, common predisposing factors were young age, smoking, illicit drugs and alcohol. The lead presenting symptoms were dyspnoea, chest pain, vomiting and cough. Of the 13 different admitting specialties, respiratory and upper gastrointestinal surgery were most common. Of those patients diagnosed with SP, 37 (54%) patients underwent imaging to exclude oesophageal injury; 30 (43%) were assessed using CT with oral contrast, 16 (23%) had a fluoroscopic contrast oesophagram, and 9 were investigated with both modalities. Conclusions: SP is uncommon, benign and does not require operative intervention. Multiple specialities manage SP at our institution and the use of imaging modalities differs between teams. We propose a management algorithm to assist clinicians unfamiliar with SP, risk-stratify patients for oesophageal injury and avoid unnecessary investigation.